Pelatihan Copywriting dan Strategi Konten untuk Menarik Minat Konsumen pada UKM RedRoseFlorist - Wati, Atika; Pratama, Reza Hardian; Nurhayati, Andini; Sari, Andini Sifa Oktiana; Febywasila, Aulia (Welfare : Jurnal Pengabdian Masyarakat, 2024)
RedRoseFlorist, an SME engaged in floristry, faces challenges in attracting consumer interest amidst increasingly competitive market competition. One of the main obstacles is the lack of skills in creating attractive and effective marketing content. This community service activity aims to provide training on copywriting and content strategy to increase RedRoseFlorist's marketing appeal. The implementation method includes theoretical training sessions on the basic principles of copywriting, creating audience-based content strategies, and hands-on practice in designing visual and written content for social media. The results of the activity showed an increase in participants' abilities in creating visually and emotionally attractive content, as well as understanding relevant marketing strategies for their target audience. With this training, RedRoseFlorist is expected to be able to increase engagement on social media and expand its market reach, so that it can compete more effectively in the floristry market.